Developing a Model for the Establishment of the Hospice Care Delivery System for Iranian Adult Patients With Cancer - Beiranvand, Samira; Rassouli, Maryam; Hazrati, Maryam; Molavynejad, Shahram; Hojjat, Suzanne; Zarea, Kourosh (Frontiers in Psychology, 2022)
Introduction: Making appropriate plans for the provision of hospice care is considered a perceived need in the Iranian health system. The current study aimed to develop a model for establishing hospice care delivery system for the adult patients with cancer. Materials & Methods: This Health System Policy Research (HSPR) utilized a mixed qualitative-quantitative approach and was conducted in 4 phases. At the first phase, a qualitative study was conducted which explained the care needs and the requirements for establishing this system from the stakeholders’ perspective (directed content analysis). The second phase aimed to examine the current situation of hospice care delivery in Iran and identify and determine the similarities and differences among them in the selected countries (comparative study). At the third phase, the main areas of the model and the related indicators were extracted and prioritized by consulting with experts ( Delphi survey). Then the model was formulated. At the fourth phase, the proposed model was validated and finalized in terms of importance, scientific acceptability, and feasibility. Results: Based on the results of the qualitative and the comparative studies, seven major domains of the model included the need to provide a variety of settings and services, comprehensive care plan, integration into the health system, specialized manpower, organizing the accountability system, laying the groundwork in the health system, and capacity building in the community. According to experts, out of 127 indicators proposed in the third phase, 102 indicators had a high priority. The proposed model had high scientific importance and acceptability and moderate feasibility. Conclusion: The first and the most important step in establishing the hospice care delivery system is laying the groundwork in the health system which requires focusing on policymaking. It is necessary to establish hospice centers and implement public awareness raising programs, train and supply expert manpower, strengthen family physician and referral process, formulate clinical guidelines, encourage the private sector and NGOs to invest, develop end-of-life and hospice care service packages, and create quality care indicators. This model can be used as a model tailored to the current state of the health system and community in Iran.